BACTERIAL COLONY GROWTH IN THE VENTILATOR CIRCUIT OF THE INTENSIVE OBSERVATION UNIT AT RSUD Dr. SOETOMO SURABAYA - Perdhana, Fajar; Utariani, Arie; Semedi, Bambang Pujo; Setiawan, Philia (Institute of Topical Disease Universitas Airlangga, 2016)
Ventilator-associated pneumonia (VAP) remains a problem with the highest cos, morbidity and mortalityt in the Intensive Care Unit (ICU). The correlation between mechanical ventilation and pneumonia is considered as common sense, yet scientific evidence to support this statement is still needed. This research aims to analyze the bacterial colony grows in mechanical ventilation circuit and those grew in the patient's sputum culture. We performed an observational study. Samples for bacterial culture were taken from ventilator circuit and patient sputum on Day-0, Day-3 and Day-7. Sputum samplings are collected using double catheter tracheal aspiration technique; Results are then analyzed with Chi-square test. While the similarity of bacteria species in ventilator circuit to patient's sputum is analyzed with Binomial test. Two samples are dropped out immediately due to the rate of bacterial growth on Day-0. Bacterial colony growth in ventilator circuit shows a significant difference on Day-3 and Day-7 at 50% and 92% respectively (p = 0.05). A comparison for the bacterial similarity of the ventilator circuit and patient's sputum shows that the bacterial growth on Day-3 is 7 out of 14 (50%) and 3 with more than 105 CFU/ml colony; while on Day-7, there are 13 out of 14 positive bacterial growth, both in the circuit and the patient's sputum. Among them, 5 out of 14 (35%) of the bacterial colony which grow in the circuit have the same species as those grow in patient's sputum. The recent study shows that there is bacteria colony growth in the ventilator circuit after Day-3 and a significant increase on Day-7. Almost half of the colony illustrates similar species from both ventilator circuit and patient's sputum. This suggests that the bacterial growth on Day-7 in the ventilator circuit might be related to those growth in patient's sputum.